Methodology to estimate the soil heterogeneity coefficient, the number of repetitions and the optimum plot size for common bean (phaseolus vulgaris l.) research (2012)
With the aim to estimate the coefficient of soil heterogeneity (b) =ithout performing tests of uniformity, we proposed a methodology to use data from yield experiments insolating the treatment effect of the response variable. To identify methodological issues and illustrate the statistical proceeding manage- ment, data from one of the yield trials conducted in common bean by the Andean Breeding Program of CIAT =ere used. The coefficient of soil heterogeneity =as estimated using the la= of variance of Smith (+958) and the equation proposed by Federer (+9D5). Ealues of G.59 and G.DD respectively =ere obtained. Finally, =e used the methodology of Hathe=ay (+9D+) and the LbM value estimated based on Federer (+9D5) to find the best combination of plot size, number of repetitions and difference to be detected as a mean percentage.